Production of compounds by phytopathogenic fungi for biological control of aquatic macrophytes. (September 2018) - Moreira, Cristiano Daniel; Scapini, Thamarys; Muller, Siliandra; Amroginski, Jéssica; Golunski, Simone; Pandolfi, Leonardo; Galon, Leandro; Jacques, Rodrigo Josemar Seminoti; de Andrade, Nariane; Bevilacqua, Caroline Borges; Mazutti, Márcio Antônio; Fongaro, Gislaine; et al.
Abstract: The intense urbanization and use of natural resources has been causing disturbances in the aquatic ecosystem, such as the disorderly and dense increase of macrophytes, such as Eichhornia crassipes, Pistia stratiotes and Salvinia herzogii . In this context, we aim to evaluate the biological control of these plants by the production of phytopathogenic fungi compounds isolated from the foliar lesions of the plants collected. The microorganisms were isolated and identified as Aspergillus flavus and Aspergillus miniscleroti . Afterwards, an experimental design was developed and the results showed that temperature and glucose concentration were determinant in biomass production, being the largest biomass obtained 26.12 g/L and 45.95 g/L for A . flavus and A . miniscleroti, respectively. The application of the compounds in the plants showed satisfactory results, presenting toxicity potential in macrophytes, with a maximum deterioration of 88–94% for macrophytes E . crassipes . Highlights: Use of A . flavus and A . minisclerotti for biological control of aquatic macrophytes. Experimental design for optimization of fungi extract. Deterioration of 88–94% for macrophytes E . crassipes .